Techniques of Vocabulary Development in Select Readings - Ibrahim Mohammed Ali Murad (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
Enriching second language learners with vocabulary is an essential part of the teaching process of English as a second/foreign language. For this aim, many books have been published in the domain—each with a particular set of techniques. Select Readings, a series of 4 levels, is an example of such books. The levels are elementary, pre-intermediate, intermediate, and upper-intermediate. This paper has selected the intermediate level as a sample to analyze the techniques adopted by the authors to achieve their purpose. Thus, each technique is identified, traced in each chapter, and all the instances are covered. The value of each technique is also sketched out. This study can aid both teachers and learners to have a better understanding and more integrated comprehension of the new vocabulary presented in the reading passages.